The development of a coding scheme to analyse argumentative utterances during group-work. (June 2020) - Larrain, Antonia; Freire, Paulina; Strasser, Katherine; Grau, Valeska
Highlights: Analysing face-to-face peer-group classroom argumentation is challenging. There are available schemes, but psychometric properties are often not reported. We developed a coding scheme which unit of analysis is argumentative utterances. The coding scheme is reliable and valid. The coding scheme enable relating individual participation to learning measures. Abstract: The relationship between peer argumentation and thinking and conceptual development has increasingly caught the attention of scholars since the work of Piaget. Analysing face-to-face peer-group classroom argumentation is challenging. There are very good analytic frameworks, but their usefulness for analysing large corpora and conducting quantitative analysis is not clear, as reliability and validity measures are often not reported. The aim of this paper is to describe the development and psychometric properties of a coding scheme to analyse argumentative moves during group-work interaction. The coding scheme was used to analyse 321 videos of fourth-grade students' group work during science lessons (unit of Forces) oriented by the same instructional design. Evidence was gathered during three experimental studies randomized at class level. We ran reliability and validity analyses. The results suggest that the coding scheme can be reliable used (in terms of both inter-rater and scale reliability) and allow to make valid inferences, and can be used to systematically relate both individual and group argumentation to individual outcomes.